Horizontal Monitoring in Austria: subjective representations by tax officials and company employees - Janina Enachescu; Maximilian Zieser; Eva Hofmann; Erich Kirchler (Business Research, 2019)
The implementation of Horizontal Monitoring (HM) in Austria represents a shift in the prevailing command-and-control paradigm towards enhanced cooperation between taxpayers and tax authorities. In the present paper, we assess how HM is perceived by different stakeholder groups when it was introduced as a pilot project embedded in the 'Fair Play Initiative' launched by the Austrian Ministry of Finance. We collected quantitative and qualitative data from tax auditors and staff of tax offices responsible for large-scale enterprises who were either directly involved or not involved in the HM pilot project, from employees of participating enterprises as well as from employees of enterprises which did not participate in the project. Results show that representations of HM were most positive among employees from HM companies and tax officials directly involved, whereas participants from the tax administration who did not take part in the project were skeptical at the beginning and remained skeptical over time. As shown in organizational change studies, the acceptance or resistance regarding the paradigm change represented by HM may originate from uncertainty and misperceptions of its goals and strategies and from speculations, particularly by poorly informed members.
Keywords: 650; Tax compliance; Horizontal monitoring; Cooperative compliance; Organizational change